A Thematic Study of Fundamental Social Principles in the Holy Quran - Hafiz Muhammad Hassan Malick (Journal of Religion and Society, 2025)
This study A Thematic Study of the Basic Social principles in the Holy Quran examines the basic socio-ethical and moral precepts as propounded in the Quran and that constitute an ideal Islamic community. The analysis upon which the study is founded is developed on the basis of the major principles of justice, equality, benevolence, trust, kinship, economic balance, peace, cooperation, freedom of opinion, human rights, moral values, knowledge, responsibility, patience, and reliance on Allah. This study commences with Justice and Fairness as the main principle of Islamic society, in the sense that justice is not just a law of the land, but it is a commandment of God and it cuts across board in the society. The second principle is equality and human dignity which is discussed within the context of Quranic rejection of racial, tribal, and class superiority and acknowledgment of natural dignity of each human being. Principle number three, which is entitled Benevolence and Compassion, deals with Quranic encouragement of helping the poor, orphans, and the needy. Faith and integrity are addressed as the core of person-to-person and financial transactions. Likewise, the rights of the relatives and neighbors as the topic of the theme, namely, the rights of kinship and social cohesion, are examined as a means to enforcing the social tissue. The paper further explores economic justice that involves assessment of the Quranic system of providing zakat and equitable distribution of wealth. Peace and reconciliation are also brought out as being key to resolving conflict, whereas cooperation on good and avoidance of evil is brought out in a group responsibility. The study also speaks about the freedom of opinion, the significance of consultative government and negation of oppressive rule. Also, moral values of honesty, modesty, patience, knowledge-seeking and accountability are depicted as bars to individual and social development. All the principles are substantiated by the Quran verses and classical and modern exegeses and scholarly sources. The conclusion which the study makes is that these social ideals, when practically used, can provide peace, justice and moral vigor in contemporary societies and that the guidance given in the Quran cannot be disregarded as it has always been relevant. Keywords: Social Justice, Islamic Ethics, Quranic Principles, Human Rights in Islam, Islamic Society, Economic Equity, Social Reform in the Quran